Delayed degeneration of the left fornical crus with verbal memory impairment in a patient with mild traumatic brain injury: A case report. Issue 51 (December 2017) - Jang, Sung Ho; Seo, Jeong Pyo
Abstract: Rationale: We report on a patient who showed delayed degeneration of the left fornical crus with verbal memory impairment following mild traumatic brain injury (TBI), which was demonstrated by diffusion tensor tractography (DTT). Patient concerns: fter flexion and hyperextension of her head to the opposite side, the patient experienced a dazed feeling for a while at the time of head trauma. The patient's Glasgow Coma Scale score was 15, and mini-mental state examination score was 30. Diagnoses: A 50-year-old right-handed female with 12 years of education suffered from head trauma resulting from a car accident. Interventions: A The patient showed normal memory function at one year after onset: the Memory Assessment Scale (global memory: 124 (95 percentile (%ile)), verbal memory: 111 (77%ile), and visual memory: 132 (98%ile) (A percentile is a measure used in statistics indicating the value below which a given percentage of observations in a group of observations fall). However, the patient began to experience decline of memory function such as forgetfulness at approximately 1.5 years after onset. On the 2-year evaluation, she showed decrement of memory function (global memory: 108 (70%ile), verbal memory: 86 (18%ile), and visual memory: 129 (97%ile). Outcomes: On 1-year DTT, the integrity of the fornix was well preserved between the fornical column and fornical crus. However, on 2-year DTT, a discontinuation was observed in the left fornical crus. Lessons: Delayed degeneration of the left fornical crus was demonstrated in a patient who showed delayed onset of verbal memory impairment following mild TBI.